Rapid prototyping of ion-selective electrodes using a low-cost 3D printed internet-of-things (IoT) controlled robot - Ozer, Tugba; Agir, Ismail; Henry, Charles S. (ELSEVIER, 2022)
We report automated fabrication of solid-contact sodium-selective (Na+-ISEs) and potassium-selective electrodes (K+-ISEs) using a 3D printed liquid handling robot controlled with Internet of Things (IoT) technology. The printing system is affordable and can be customized for the use with micropipettes for applications such as drop-casting, biological assays, sample preparation, rinsing, cell culture, and online analyte monitoring using multiwell plates. The robot is more compact (25 x 30 x 35 cm) and user-friendly than commercially available systems and does not require mechatronic experience. For fabrication of ion-selective electrodes, a carbon black intermediate layer and ion-selective membrane were successively drop-cast on the surface of stencil-printed carbon electrode using the dispensing robot. The 3D-printed robot increased ISE robustness while decreasing the modification time by eliminating manual steps. The Na+-ISEs and K+-ISEs were characterized for their potentiometric responses using a custom-made, low-cost (<$25) multi-channel smartphone-based potentiometer capable of signal processing and wireless data transmission. The electrodes showed Nernstian responses of 58.2 +/- 2.6 mV decade(-1) and 56.1 +/- 0.7 mV decade 1 for Na+ and K+, respectively with an LOD of 1.0 x 10(-5) M. We successfully applied the ISEs for multiplexed detection of Na+ and K+ in urine and artificial sweat samples at clinically relevant concentration ranges. The 3D-printed pipetting robot cost $100 and will pave the way for more accessible mass production of ISEs for those who cannot afford the expensive commercial robots.
Keywords: 3D-printing; Internet-of-things (IoT); Solid-contact ion-selective electrode; Potassium; Sodium; Potentiometric detection; Point-of-care; IMPRINTED MESOPOROUS CARBON; SOLID-CONTACT; WATER LAYER; SENSOR; HYPONATREMIA; DISORDERS; URINE; Chemistry